Superresolution Imaging Captures Carbohydrate Utilization Dynamics in Human Gut Symbionts - Krishanthi S. Karunatilaka (American Society for Microbiology, 2014)
ABSTRACT Gut microbes play a key role in human health and nutrition by catabolizing a wide variety of glycans via enzymatic activities that are not encoded in the human genome. The ability to recognize and process carbohydrates strongly influences the structure of the gut microbial community. While the effects of diet on the microbiota are well documented, little is known about the molecular processes driving metabolism. To provide mechanistic insight into carbohydrate catabolism in gut symbionts, we studied starch processing in real time in the model Bacteroides thetaiotaomicron starch utilization system (Sus) by single-molecule fluorescence. Although previous studies have explored Sus protein structure and function, the transient interactions, assembly, and collaboration of these outer membrane proteins have not yet been elucidated in live cells. Our live-cell superresolution imaging reveals that the polymeric starch substrate dynamically recruits Sus proteins, serving as an external scaffold for bacterial membrane assembly of the Sus complex, which may promote efficient capturing and degradation of starch. Furthermore, by simultaneously localizing multiple Sus outer membrane proteins on the B. thetaiotaomicron cell surface, we have characterized the dynamics and stoichiometry of starch-induced Sus complex assembly on the molecular scale. Finally, based on Sus protein knockout strains, we have discerned the mechanism of starch-induced Sus complex assembly in live anaerobic cells with nanometer-scale resolution. Our insights into the starch-induced outer membrane protein assembly central to this conserved nutrient uptake mechanism pave the way for the development of dietary or pharmaceutical therapies to control Bacteroidetes in the intestinal tract to enhance human health and treat disease. IMPORTANCE In this study, we used nanometer-scale superresolution imaging to reveal dynamic interactions between the proteins involved in starch processing by the prominent human gut symbiont Bacteroides thetaiotaomicron in real time in live cells. These results represent the first working model of starch utilization system (Sus) complex assembly and function during glycan catabolism and are likely to describe aspects of how other Sus-like systems function in human gut Bacteroidetes. Our results provide unique mechanistic insights into a glycan catabolism strategy that is prevalent within the human gut microbial community. Proper understanding of this conserved nutrient uptake mechanism is essential for the development of dietary or pharmaceutical therapies to control intestinal tract microbial populations, to enhance human health, and to treat disease.